Optimization of the conditions for rice bran phytate degradation by their own phytases - Farouk, Abd-El Aziem; Ahamed, N. Thoufeek; Meor Hussin, Anis Shobirin; Al Zahrani, Othman; Alotaibi, Saqer (Open Science Publishers, 2018)
The rice bran by-product of rice during milling process chemically contains moisture, ash, crude protein (12%), crude fat (15%), crude fiber 7%, crude carbohydrate (31.1%), and energy. It contains high phytate and dietary fiber contents. The cereal whole paddy after milling produces 8% of rice bran. Rice bran amino acid profile has been normally suggested to be superior to cereal grain proteins. Existing phytase within the rice bran generally improves phytate phosphorus utilizations. The present study has been conducted to find the effect of phytase activity of rice bran against five different temperatures and also the effect of phytase activity of rice bran against five different temperatures at optimum pH 5.5. The results showed that as the concentration of rice bran increases from 0 to 20%, the phytase activity also increased. The optimum phytase activity was found at 10% concentration of rice bran at 37°C. Moreover, an increase in phytase activity at the same concentration of rice bran was observed while adjusting the pH at pH 5.5. The four concentrations of rice bran showed gradual increase in activity at 50°C which was directly proportional to the concentrations of rice bran and comparatively better while adjusting the pH at pH 5.5. Around two-fold increase in activity was observed at room temperature and 50°C when the concentration of rice bran was increased from 5 to 20% with and without pH 5.5 adjustments.